Thành phần hóa học và hoạt tính gây độc tế bào của lá cây Vót dạng cơm cháy Viburnum sambucinum (Caprifoliaceae) - Trà, Nguyễn Thanh; Ngân, Trương Bích; Mai Hương, Đoàn Thị; Thảo, Đỗ Thị; Litaudon, Marc; Hùng, Nguyễn Văn; Minh, Châu Văn; Cường, Phạm Văn (Vietnam Journal of Chemistry, 2016)
Viburnum sambucinum is a small woody tree belongs to the genus Viburnum (Caprifoliaceae), mainly distributed in Vietnam, Lao and Cambodia. Extensive studies of the genus Viburnum have led to the identification of many compounds, such as diterpenes, triterpenes, iridoids, monoterpenes, sesquiterpenes, flavonoids, lignans, etc. In previous study, we reported 6 terpenoids isolated from the leaves of Viburnum sambucinum. In this study, we describe the isolation and structural characterizations of four compounds hupehenol D (1), hupehenol A (2), 12β-hydoxy-3,15-dioxo- 20,21,22-23,24,25,26,27-octanordammanran (3), luteolin (4) and in vitro cytotoxic activities of ten compounds (1-10) from the leaves of Viburnum sambucinum. Compound 1 and 3 exhibited significant cytotoxic activity against 4 cancer cell lines with IC50 value 4.71±0.03-5.35±0.04 μM. The compounds 2, 4, 6, 7 and 9 displayed week cytotoxicity with IC50 values ranging from 9.31± 0.12 to 82.06±0.94 mM.